PHYTOCHEMICALAND ANTIMICROBIAL SCREENING OF THE STEM BARKEXTRACTS OF PTEROCARPUSERINACEUS (POIR) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Medicinal plants are very rich in phytochemicals and have been widely used in modern-day processing drugs. Pterocarpus Erinaceus and has been commonly utilized in Nigerian folk medicine to treat various illnesses such as diarrhea, dysentery, urethral discharges, fever. In this study, the phytochemical constituents and antimicrobial activities of Pterocarpus Erinaceus were analyzed. The result of the phytochemical analysis revealed the presence of tannins, saponins, and flavonoids. The antimicrobial screening showed that the plant is active against Salmonella typhi, Klebsiella pneumoniae, Enterobacter aerogenes, Enterococcus faecalis, and Escherichia coli.